Pillar[5]arene-based dually crosslinked supramolecular gel as a sensor for the detection of adiponitrile - Rodin, Maksim; Helle, David; Kuckling, Dirk (Polymer Chemistry)
An SPR-based dually crosslinked gel sensor for adiponitrile bearing pillar[5]arene responsive sites with a low limit of detection was developed.
Keywords: Organic Chemistry; Polymers and Plastics; Biochemistry; Bioengineering

Experimental Investigations of Carbon Fiber Reinforced Polymer Composites and Their Constituents to Determine Their Elastic Material Properties and Complementary Inhomogeneous Experiments with Local Strain Considerations - Penner, Eduard; Caylak, Ismail; Mahnken, Rolf (Fibers and Polymers)
Abstract Composite materials, such as fiber reinforced polymers, become increasingly important due to their excellent mechanical and lightweight properties. In this respect, this paper reports the characterization of a unidirectional carbon fiber reinforced polymer composite material. Particularly, the mechanical behavior of the overall composite and of the individual constituents of the composite is investigated. To this end, tensile and shear tests are performed for the composite. As a result, statistics for five transversely isotropic material parameters can be established for the composite. For the description of the mechanical properties of the constituents, tensile tests for the carbon fiber as well as for the polymer matrix are carried out. In addition, the volume fraction of fibers in the matrix is determined experimentally using an ashing technique and Archimedes’ principle. For the Young’s modulus of the fiber, the Young’s modulus and transverse contraction of the matrix, as well as the volume fraction of the constituents, statistics can be concluded. The resulting mechanical properties on both scales are useful for the application and validation of different material models and homogenization methods. Finally, in order to validate the obtained properties in the future, inhomogeneous tests were performed, once a flat plate with a hole and a flat plate with semicircular notches.
Keywords: Polymers and Plastics; General Chemical Engineering; General Chemistry

Developing Quantitative Nondestructive Characterization of Nanomaterials: A Case Study on Sequential Infiltration Synthesis of Block Copolymers - Cara, Eleonora; Hönicke, Philipp; Kayser, Yves; Lindner, Jörg K. N.; Castellino, Micaela; Murataj, Irdi; Porro, Samuele; Angelini, Angelo; De Leo, Natascia; Pirri, Candido Fabrizio; Beckhoff, Burkhard; Boarino, Luca; et al. (ACS Applied Polymer Materials)
Keywords: Organic Chemistry; Polymers and Plastics; Process Chemistry and Technology

Morphological and mechanical properties of foamed thick-walled Wood-Plastic-Composite structures - Moritzer, Elmar; Flachmann, Felix (Journal of Cellular Plastics)
Microcellular wood fiber reinforced polymers offer the possibility to reduce the use of fossil raw materials. In particular, thick-walled structures with thicknesses greater than 6 mm offer a high potential for weight savings. This study investigates the cell structures and mechanical properties of injection-molded test specimens. The influence of different thicknesses (6–10 mm) along with different chemical blowing agents (endothermic, exothermic) with varying dosages (0–2 wt%) is analyzed. The investigations reveal that exothermic chemical blowing agents form finer cells consistently to thin-walled structures than endothermic ones. Higher foaming agent content leads to higher pore fractions, with many small cells coalescing into a large open-pore cell network. The mechanical properties depend mainly on the pore content of the sample. The specific tensile properties deteriorate with the use of chemical blowing agents (CFA), whereas the sandwich structure produced with compact edge layers has a positive influence on the specific flexural properties.
Keywords: Materials Chemistry; Polymers and Plastics; General Chemistry

Adaptive Scaling of Components in the Fused Deposition Modeling Process - Moritzer, Elmar; Hecker, Felix (Macromolecular Symposia)
Abstract Currently, the fused deposition modeling (FDM) process is the most common additive manufacturing technology. The principle of the FDM process is the strand wise deposition of molten thermoplastic polymers, by feeding a filament trough a heated nozzle. Due to the strand and layer wise deposition the cooling of the manufactured component is not uniform. This leads to dimensional deviations which may cause the component to be unusable for the desired application. In this paper, a method is described which is based on the shrinkage compensation through the adaption of every single raster line in components manufactured with the FDM process. The shrinkage compensation is based on a model resulting from a DOE which considers the main influencing factors on the shrinkage behavior of raster lines in the FDM process. An in‐house developed software analyzes the component and locally applies the shrinkage compensation with consideration of the boundary conditions, e.g., the position of the raster line in the component and the process parameters. Following, a validation using a simple geometry is conducted to show the effect of the presented adaptive scaling method.
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry; Condensed Matter Physics

Adaptive Scaling of Components in the Fused Deposition Modeling Process - Moritzer, Elmar; Hecker, Felix (Macromolecular Symposia)
Abstract Currently, the fused deposition modeling (FDM) process is the most common additive manufacturing technology. The principle of the FDM process is the strand wise deposition of molten thermoplastic polymers, by feeding a filament trough a heated nozzle. Due to the strand and layer wise deposition the cooling of the manufactured component is not uniform. This leads to dimensional deviations which may cause the component to be unusable for the desired application. In this paper, a method is described which is based on the shrinkage compensation through the adaption of every single raster line in components manufactured with the FDM process. The shrinkage compensation is based on a model resulting from a DOE which considers the main influencing factors on the shrinkage behavior of raster lines in the FDM process. An in‐house developed software analyzes the component and locally applies the shrinkage compensation with consideration of the boundary conditions, e.g., the position of the raster line in the component and the process parameters. Following, a validation using a simple geometry is conducted to show the effect of the presented adaptive scaling method.
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry; Condensed Matter Physics

Antimicrobial Brushes on Titanium via “Grafting to” Using Phosphonic Acid/Pyridinium Containing Block Copolymers - Methling, Rafael; Dückmann, Oliver; Simon, Frank; Wolf‐Brandstetter, Cornelia; Kuckling, Dirk (Macromolecular Materials and Engineering)
Abstract Coating medical implants with antibacterial polymers may prevent postoperative infections which are a common issue for conventional titanium implants and can even lead to implant failure. Easily applicable diblock copolymers are presented that form polymer brushes via “grafting to” mechanism on titanium and equip the modified material with antibacterial properties. The polymers carry quaternized pyridinium units to combat bacteria and phosphonic acid groups which allow the linear chains to be anchored to metal surfaces in a convenient coating process. The polymers are synthesized via reversible‐addition‐fragmentation‐chain‐transfer (RAFT) polymerization and postmodifications and are characterized using NMR spectroscopy and SEC. Low grafting densities are a major drawback of the “grafting to” approach compared to “grafting from”. Thus, the number of phosphonic acid groups in the anchor block are varied to investigate and optimize the surface binding. Modified titanium surfaces are examined regarding their composition, wetting behavior, streaming potential, and coating stability. Evaluation of the antimicrobial properties revealed reduced bacterial adhesion and biofilm formation for certain polymers, albeit the cell biocompatibility against human gingival fibroblasts is also impaired. The presented findings show the potential of easy‐to‐apply polymer coatings and aid in designing next‐generation implant surface modifications.
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry; General Chemical Engineering

Bauteilschonendes Entfügen struktureller Klebverbindungen durch Kälte - Chudalla, Nick; Meschut, Gerson; Bartley, Aurélie; Wibbeke, Tim Michael (adhäsion KLEBEN & DICHTEN)
Keywords: Polymers and Plastics; General Chemical Engineering; General Chemistry

Influence of surface activation on the microporosity of PE‐CVD and PE‐ALD SiO x thin films on PDMS - Hoppe, Christian; Mitschker, Felix; Mai, Lukas; Liedke, Maciej Oskar; Arcos, Teresa; Awakowicz, Peter; Devi, Anjana; Attallah, Ahmed Gamal; Butterling, Maik; Wagner, Andreas; Grundmeier, Guido (Plasma Processes and Polymers)
Keywords: Polymers and Plastics; Condensed Matter Physics

Comparative analysis of hexamethyldisiloxane and hexamethyldisilazane plasma polymer thin films before and after plasma oxidation - Xie, Xiaofan; de los Arcos, Teresa; Grundmeier, Guido (Plasma Processes and Polymers)
Keywords: Polymers and Plastics; Condensed Matter Physics

Warmforming Flow Pressing Characteristics of Continuous Fibre Reinforced Thermoplastic Composites - Gröger, Benjamin; Römisch, David; Kraus, Martin; Troschitz, Juliane; Füßel, René; Merklein, Marion; Gude, Maik (Polymers)
The paper presents research regarding a thermally supported multi-material clinching process (hotclinching) for metal and thermoplastic composite (TPC) sheets: an experimental approach to investigate the flow pressing phenomena during joining. Therefore, an experimental setup is developed to compress the TPC-specimens in out-of-plane direction with different initial TPC thicknesses and varying temperature levels. The deformed specimens are analyzed with computed tomography to investigate the resultant inner material structure at different compaction levels. The results are compared in terms of force-compaction-curves and occurring phenomena during compaction. The change of the material structure is characterized by sliding phenomena and crack initiation and growth.
Keywords: Polymers and Plastics; General Chemistry

Hydrogel-Based Biosensors - Völlmecke, Katharina; Afroz, Rowshon; Bierbach, Sascha; Brenker, Lee Josephine; Frücht, Sebastian; Glass, Alexandra; Giebelhaus, Ryland; Hoppe, Axel; Kanemaru, Karen; Lazarek, Michal; Rabbe, Lukas; Song, Longfei; et al. (Gels)
There is an increasing interest in sensing applications for a variety of analytes in aqueous environments, as conventional methods do not work reliably under humid conditions or they require complex equipment with experienced operators. Hydrogel sensors are easy to fabricate, are incredibly sensitive, and have broad dynamic ranges. Experiments on their robustness, reliability, and reusability have indicated the possible long-term applications of these systems in a variety of fields, including disease diagnosis, detection of pharmaceuticals, and in environmental testing. It is possible to produce hydrogels, which, upon sensing a specific analyte, can adsorb it onto their 3D-structure and can therefore be used to remove them from a given environment. High specificity can be obtained by using molecularly imprinted polymers. Typical detection principles involve optical methods including fluorescence and chemiluminescence, and volume changes in colloidal photonic crystals, as well as electrochemical methods. Here, we explore the current research utilizing hydrogel-based sensors in three main areas: (1) biomedical applications, (2) for detecting and quantifying pharmaceuticals of interest, and (3) detecting and quantifying environmental contaminants in aqueous environments.
Keywords: Polymers and Plastics; Organic Chemistry; Biomaterials; Bioengineering

Thin Organic‐Inorganic Anti‐Fouling Hybrid‐Films for Microreactor Components - Neßlinger, Vanessa; Welzel, Stefan; Rieker, Florian; Meinderink, Dennis; Nieken, Ulrich; Grundmeier, Guido (Macromolecular Reaction Engineering)
Keywords: Polymers and Plastics; General Chemical Engineering; General Chemistry

Influence of surface activation on the microporosity of PE‐CVD and PE‐ALD SiO x thin films on PDMS - Hoppe, Christian; Mitschker, Felix; Mai, Lukas; Liedke, Maciej Oskar; de los Arcos de Pedro, Maria Teresa; Awakowicz, Peter; Devi, Anjana; Attallah, Ahmed Gamal; Butterling, Maik; Wagner, Andreas; Grundmeier, Guido (Plasma Processes and Polymers)
Keywords: Polymers and Plastics; Condensed Matter Physics

Comparative analysis of hexamethyldisiloxane and hexamethyldisilazane plasma polymer thin films before and after plasma oxidation - Xie, Xiaofan; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Plasma Processes and Polymers)
Keywords: Polymers and Plastics; Condensed Matter Physics

Targeted Synthesis of the Type-A Particle Substructure from Enzymatically Produced Eumelanin - Büngeler, Anne; Kollmann, Fabian; Huber, Klaus; Strube, Oliver I. (Biomacromolecules)
Keywords: Materials Chemistry; Polymers and Plastics; Biomaterials; Bioengineering

Untersuchung von Klebverbindungen für Batteriegehäuse - Schmolke, Tobias; Meschut, Gerson; Meinderink, Dennis; Rieker, Florian; Grundmeier, Guido (adhäsion KLEBEN & DICHTEN)
Keywords: Polymers and Plastics; General Chemical Engineering; General Chemistry

Low Temperature Laser Sintering with PA12 and PA6 on a Standard System - Menge, Dennis; Schmid, Hans-Joachim (Macromolecular Symposia)
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry; Condensed Matter Physics

Development of a test method for investigating the leak tightness of hybrid joined battery housing connections - Schmolke, Tobias; Teutenberg, Dominik; Meschut, Gerson (International Journal of Adhesion and Adhesives)
Keywords: Polymers and Plastics; General Chemical Engineering; Biomaterials

Influence of Processing Glass-Fiber Filled Plastics on Different Twin-Screw Extruders and Varying Screw Designs on Fiber Length and Particle Distribution - Rüppel, Annette; Wolff, Susanne; Oldemeier, Jan Philipp; Schöppner, Volker; Heim, Hans-Peter (Polymers)
Due to their valuable properties (low weight, and good thermal and mechanical properties), glass fiber reinforced thermoplastics are becoming increasingly important. Fiber-reinforced thermoplastics are mainly manufactured by injection molding and extrusion, whereby the extrusion compounding process is primarily used to produce fiber-filled granulates. Reproducible production of high-quality components requires a granulate in which the fiber length is even and high. However, the extrusion process leads to the fact that fiber breakages can occur during processing. To enable a significant quality enhancement, experimentally validated modeling is required. In this study, short glass fiber reinforced thermoplastics (polypropylene) were produced on two different twin-screw extruders. Therefore, the machine-specific process behavior is of major interest regarding its influence. First, the fiber length change after processing was determined by experimental investigations and then simulated with the SIGMA simulation software. By comparing the simulation and experimental tests, important insights could be gained and the effects on fiber lengths could be determined in advance. The resulting fiber lengths and distributions were different, not only for different screw configurations (SC), but also for the same screw configurations on different twin-screw extruders. This may have been due to manufacturer-specific tolerances.
Keywords: Polymers and Plastics; General Chemistry

Altering of lower critical solution temperature of environmentally responsive poly (N-isopropylacrylamide-co-acrylic acid-co-vanillin acrylate) affected by acrylic acid, vanillin acrylate, and post-polymerization modification - Abdelaty, Momen S. A.; Kuckling, Dirk (Colloid and Polymer Science)
Keywords: Materials Chemistry; Colloid and Surface Chemistry; Polymers and Plastics; Physical and Theoretical Chemistry

A combinatorial study of electrochemical anion intercalation into graphite - Chugh, Manjusha; Jain, Mitisha; Wang, Gang; Nia, Ali Shaygan; Mirhosseini, Hossein; Kühne, Thomas (Materials Research Express)
Abstract Dual-ion batteries are considered to be an emerging viable energy storage technology owing to their safety, high power capability, low cost, and scalability. Intercalation of anions into a graphite positive electrode provides high operating voltage and improved energy density to such dual-ion batteries. In this work, we have performed a combinatorial study of graphite intercalation compounds considering four anions, namely hexafluorophosphate (PF <?CDATA ${}_{6}^{-}$?> 6 − ), perchlorate (ClO <?CDATA ${}_{4}^{-}$?> 4 − ), bis(fluorosulfonyl)imide (FSI − ), and bis(trifluoromethanesulfonyl)imide (TFSI − ), via first-principles calculations. The structural properties and energetics of the intercalation compounds are compared based on different sizes, geometries, and the physical and chemical properties of the intercalated anions. The staging mechanism of anion intercalation into graphite and the specific capacities, and voltage profiles of the intercalated compounds are investigated. A comparison regarding battery electrochemistry is also done with available experimental observations. Our calculated intercalation energies and voltage profiles show that the initial anion intercalation into graphite is less favorable than subsequent ones for all the anions considered in this study. Although the effect of the size of anions in a graphite cathode on various properties of the intercalated compounds is not as significant as the size of cations in a graphite anode, some distinction between the studied anions can still be made. Among the studied anions, the intercalation compounds based on PF <?CDATA ${}_{6}^{-}$?> 6 − are the most stable ones. These PF <?CDATA ${}_{6}^{-}$?> 6 − anions cause relatively small structural deformations of the graphite and have the highest oxidative ability, highest onset voltage, and highest diffusion barrier along the graphene sheets. The overall small diffusion barriers of the anions within graphite explain the high rate capability of dual-ion batteries.
Keywords: Metals and Alloys; Polymers and Plastics; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Self-Assembled Fibrinogen Hydro- and Aerogels with Fibrin-like 3D Structures - Hense, Dominik; Büngeler, Anne; Kollmann, Fabian; Hanke, Marcel; Orive, Alejandro; Keller, Adrian; Grundmeier, Guido; Huber, Klaus; Strube, Oliver I. (Biomacromolecules)
Keywords: Materials Chemistry; Polymers and Plastics; Biomaterials; Bioengineering

Multiresponsive Polymer Nanoparticles Based on Disulfide Bonds - Wagner, Maximilian; Krieger, Anja; Minameyer, Martin; Hämisch, Benjamin; Huber, Klaus; Drewello, Thomas; Gröhn, Franziska (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Dämpfungseigenschaften geklebter Verbindungen - Potenzialanalyse und Klebstoffcharakterisierung - Damm, Jannis; Albiez, Matthias; Göddecke, Johannes; Meschut, Gerson; Ummenhofer, Thomas (adhäsion KLEBEN & DICHTEN)
Keywords: Polymers and Plastics; General Chemical Engineering; General Chemistry

Carbon-Based Metal-Free Electrocatalysts: Past, Present, and Future - Zhai, Qingfeng; Pan, Ying; Dai, Liming (Accounts of Materials Research)
Keywords: Materials Chemistry; Polymers and Plastics; Materials Science (miscellaneous); Chemical Engineering (miscellaneous)

The Deterioration Mechanism of Silicone Molds in Polyurethane Vacuum Casting - Wortmann, Martin; Frese, Natalie; Keil, Waldemar; Brikmann, Johannes; Biedinger, Jan; Brockhagen, Bennet; Reiss, Günter; Schmidt, Claudia; Gölzhäuser, Armin; Moritzer, Elmar; Hüsgen, Bruno (ACS Applied Polymer Materials)
Keywords: Organic Chemistry; Polymers and Plastics; Process Chemistry and Technology

Contrast variation of micelles composed of Ca2+ and block copolymers of two negatively charged polyelectrolytes - Carl, Nico; Prévost, Sylvain; Schweins, Ralf; Huber, Klaus (Colloid and Polymer Science)
Abstract Block copolymers were prepared with two anionic polyelectrolyte blocks: sodium polyacrylate (PA) and sodium polystyrene sulfonate (PSS), in order to investigate their phase behavior in aqueous solution in the presence of Ca 2+ cations. Depending on the concentration of polymer and Ca 2+ and on the ratio of the block lengths in the copolymer, spherical micelles were observed. Micelle formation arises from the specific interaction of Ca 2+ with the PA block only. An extensive small-angle scattering study was performed in order to unravel the structure and dimensions of the block copolymer micelles. Deuteration of the PA block enabled us to perform contrast variation experiments using small-angle neutron scattering at variable ratios of light and heavy water which were combined with information from small-angle X-ray scattering and dynamic light scattering.
Keywords: Materials Chemistry; Colloid and Surface Chemistry; Polymers and Plastics; Physical and Theoretical Chemistry

Simple Determination of Fast Curing Parameters for Bonded Structures - Ditter, Jan; Aubel, Tobias; Meschut, Gerson (adhesion ADHESIVES + SEALANTS)
Keywords: Polymers and Plastics; General Chemical Engineering; General Chemistry

Joining and Disjoining Concepts for Adhesive Bonded Lightweight Structures - Ditter, Jan; Meschut, Gerson; Wibbeke, Tim Michael (adhesion ADHESIVES + SEALANTS)
Keywords: Polymers and Plastics; General Chemical Engineering; General Chemistry

Dually Cross‐Linked Supramolecular Hydrogel as Surface Plasmon Resonance Sensor for Small Molecule Detection - Li, Jie; Ji, Chendong; Yu, Xiaoqian; Yin, Meizhen; Kuckling, Dirk (Macromolecular Rapid Communications)
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry

Azlactone-functionalized smart block copolymers for organocatalyst immobilization - Yu, Xiaoqian; Herberg, Artjom; Kuckling, Dirk (European Polymer Journal)
Keywords: Organic Chemistry; Polymers and Plastics; General Physics and Astronomy; Materials Chemistry

Preparation of Light-Responsive Aliphatic Polycarbonate via Versatile Polycondensation for Controlled Degradation - Sun, Jingjiang; Anderski, Juliane; Picker, Marie-Theres; Langer, Klaus; Kuckling, Dirk (Macromolecular Chemistry and Physics)
Keywords: Materials Chemistry; Organic Chemistry; Polymers and Plastics; Physical and Theoretical Chemistry; Condensed Matter Physics

Light‐Responsive Serinol‐Based Polyurethane Nanocarrier for Controlled Drug Release - Sun, Jingjiang; Rust, Tarik; Kuckling, Dirk (Macromolecular Rapid Communications)
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry

Invertible Micelles Based on Ion-Specific Interactions of Sr2+ and Ba2+ with Double Anionic Block Copolyelectrolytes - Carl, Nico; Prévost, Sylvain; Schweins, Ralf; Houston, Judith E.; Morfin, Isabelle; Huber, Klaus (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Phase Transformation Behavior of Polylactide Probed by Small Angle Light Scattering and Calorimetry - Schmidt, Nico; Keuker‐Baumann, Susanne; Meyer, Jörg; Huber, Klaus (Journal of Polymer Science Part B: Polymer Physics)
Keywords: Materials Chemistry; Polymers and Plastics; Physical and Theoretical Chemistry; Condensed Matter Physics

Einfache Ermittlung von Schnellhärtungsparametern für elementar geklebte Strukturen - Ditter, Jan; Aubel, Tobias; Teutenberg, Dominik; Meschut, Gerson (adhäsion KLEBEN & DICHTEN)
Keywords: Polymers and Plastics; General Chemical Engineering; General Chemistry

Biomolecule Sensor Based on Azlactone‐Modified Hydrogel Films - Li, Jie; Yu, Xiaoqian; Herberg, Artjom; Kuckling, Dirk (Macromolecular Rapid Communications)
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry

Numerical study of polyethylene burning in counterflow: Effect of pyrolysis kinetics and composition of pyrolysis products - Karpov, A. I.; Korobeinichev, O. P.; Bolkisev, A. A.; Shaklein, A. A.; Shmakov, A. G.; Paletsky, A. A.; Gonchikzhapov, M. B. (Fire and Materials)
Keywords: Metals and Alloys; Polymers and Plastics; General Chemistry; Ceramics and Composites; Electronic; Optical and Magnetic Materials

The Twofold Role of 12-Hydroxyoctadecanoic Acid (12-HOA) in a Ternary Water—Surfactant—12-HOA System: Gelator and Co-Surfactant - Steck, Katja; Schmidt, Claudia; Stubenrauch, Cosima (Gels)
Gelled lyotropic liquid crystals can be formed by adding a gelator to a mixture of surfactant and solvent. If the gel network and the liquid-crystalline phase coexist without influencing each other, the self-assembly is called orthogonal. In this study, the influence of the organogelator 12-hydroxyoctadecanoic acid (12-HOA) on the lamellar and hexagonal liquid crystalline phases of the binary system H2O–C12E7 (heptaethylene glycol monododecyl ether) is investigated. More precisely, we added 12-HOA at mass fractions from 0.015 to 0.05 and studied the resulting phase diagram of the system H2O–C12E7 by visual observation of birefringence and by 2H NMR spectroscopy. In addition, the dynamic shear moduli of the samples were measured in order to examine their gel character. The results show that 12-HOA is partly acting as co-surfactant, manifested by the destabilization of the hexagonal phase and the stabilization of the lamellar phase. The higher the total surfactant concentration, the more 12-HOA is incorporated in the surfactant layer. Accordingly, its gelation capacity is substantially reduced in the surfactant solution compared to the system 12-HOA–n-decane, and large amounts of gelator are required for gels to form, especially in the lamellar phase.
Keywords: Polymers and Plastics; Organic Chemistry; Biomaterials; Bioengineering

Blends of Two Perylene Derivatives: Mesogenic Properties and Application As Emitter Materials in OLEDs - Vollbrecht, Joachim; Stepen, Arne; Nolkemper, Karlo; Keuker-Baumann, Susanne; Kitzerow, Heinz-Siegfried (Polymer Science, Series C)
Keywords: Materials Chemistry; Polymers and Plastics; General Chemistry

Elektrochemische Korrosionsprüfung - Ditz, Michael; Meschut, Gerson; Grothe, Richard; Grundmeier, Guido; Windoffer, Marcel; Kötting, Gerhard (adhäsion KLEBEN & DICHTEN)
Keywords: Polymers and Plastics; General Chemical Engineering; General Chemistry

Temperaturbedingte Relativverschiebung von Dickschichtklebungen - Mailänder, Sebastian; Meschut, Gerson (adhäsion KLEBEN & DICHTEN)
Keywords: Polymers and Plastics; General Chemical Engineering; General Chemistry

Design of elastic adhesive bonds - Mailänder, Sebastian; Meschut, Gerson (ADHESION ADHESIVES&SEALANTS)
Keywords: Polymers and Plastics; General Chemical Engineering; General Chemistry

Anodizing of electrolytically galvanized steel surfaces for improved interface properties in fiber metal laminates - Engelkemeier, Katja; Mücke, Christian; Hoyer, Kay-Peter; Schaper, Mirko (Advanced Composites and Hybrid Materials)
Keywords: Materials Chemistry; Polymers and Plastics; Materials Science (miscellaneous); Ceramics and Composites

Synthesis of Amphiphilic Block Copolymers Based on SKA by RAFT Polymerization - Yu, Xiaoqian; Picker, Marie-Theres; Schneider, Martin; Herberg, Artjom; Pascual, Sagrario; Fontaine, Laurent; Kuckling, Dirk (Macromolecular Chemistry and Physics)
Keywords: Materials Chemistry; Organic Chemistry; Polymers and Plastics; Physical and Theoretical Chemistry; Condensed Matter Physics

Structural Transitions and Thermochromism of Linear Polynuclear Cobalt(II)-4-Octadecyl-1,2,4-triazole Complexes - Bräunlich, Irene; Mair, Christiane; Bauer, Matthias; Caseri, Walter (Journal of Inorganic and Organometallic Polymers and Materials)
Keywords: Materials Chemistry; Polymers and Plastics

Polyphilic Interactions as Structural Driving Force Investigated by Molecular Dynamics Simulation (Project 7) - Peschel, Christopher; Brehm, Martin; Sebastiani, Daniel (Polymers)
We investigated the effect of fluorinated molecules on dipalmitoylphosphatidylcholine (DPPC) bilayers by force-field molecular dynamics simulations. In the first step, we developed all-atom force-field parameters for additive molecules in membranes to enable an accurate description of those systems. On the basis of this force field, we performed extensive simulations of various bilayer systems containing different additives. The additive molecules were chosen to be of different size and shape, and they included small molecules such as perfluorinated alcohols, but also more complex molecules. From these simulations, we investigated the structural and dynamic effects of the additives on the membrane properties, as well as the behavior of the additive molecules themselves. Our results are in good agreement with other theoretical and experimental studies, and they contribute to a microscopic understanding of interactions, which might be used to specifically tune membrane properties by additives in the future.
Keywords: Polymers and Plastics; General Chemistry

Alkoxide-Initiated Regioselective Coupling of Carbon Disulfide and Terminal Epoxides for the Synthesis of Strongly Alternating Copolymers - Diebler, Johannes; Komber, Hartmut; Häußler, Liane; Lederer, Albena; Werner, Thomas (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Contraction and Coagulation of Spherical Polyelectrolyte Brushes in the Presence of Ag+, Mg2+, and Ca2+ Cations - Ezhova, Anna; Huber, Klaus (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Systematic Limitations in Concentration Analysis via Anomalous Small-Angle X-ray Scattering in the Small Structure Limit - Goerigk, Guenter; Lages, Sebastian; Huber, Klaus (Polymers)
Keywords: Polymers and Plastics; General Chemistry

Polymer-stabilized blue phases: promising mesophases for a new generation of liquid crystal displays - Nordendorf, G.; Hoischen, A.; Schmidtke, J.; Wilkes, D.; Kitzerow, Heinz-Siegfried (Polymers for Advanced Technologies)
Keywords: Polymers and Plastics

Conformation and Interactions of Polystyrene and Fullerenes in Dilute to Semidilute Solutions - Dattani, Rajeev; Michels, Rolf; Nedoma, Alisyn J.; Schweins, Ralf; Westacott, Paul; Huber, Klaus; Cabral, João T. (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Specific Interactions of Ag+ Ions with Anionic Polyacrylate Chains in Dilute Solution - Ezhova, A.; Huber, Klaus (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Morphology of Blends with Cross-Linked PMMA Microgels and Linear PMMA Chains - Schneider, M.; Michels, R.; Pipich, V.; Goerigk, G.; Sauer, V.; Heim, H.-P.; Huber, Klaus (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

SAXS and ASAXS on Dilute Sodium Polyacrylate Chains Decorated with Lead Ions - Lages, Sebastian; Goerigk, Günter; Huber, Klaus (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

N,O6-partially acetylated chitosan nanoparticles hydrophobically-modified for controlled release of steroids and vitamin E - Quiñones, Javier Pérez; Gothelf, Kurt Vesterager; Kjems, Jørgen; Caballero, Ángeles María Heras; Schmidt, Claudia; Covas, Carlos Peniche (Carbohydrate Polymers)
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry

Self-assembled nanoparticles of glycol chitosan – Ergocalciferol succinate conjugate, for controlled release - Quiñones, Javier Pérez; Gothelf, Kurt Vesterager; Kjems, Jørgen; Caballero, Ángeles María Heras; Schmidt, Claudia; Covas, Carlos Peniche (Carbohydrate Polymers)
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry

Self-assembled nanoparticles of modified-chitosan conjugates for the sustained release of dl-α-tocopherol - Quiñones, Javier Pérez; Gothelf, Kurt Vesterager; Kjems, Jørgen; Yang, Chuanxu; Caballero, Angeles María Heras; Schmidt, Claudia; Covas, Carlos Peniche (Carbohydrate Polymers)
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry

Kinetics of the grating formation in holographic polymer-dispersed liquid crystals: NMR measurement of diffusion coefficients - Tang, Mingxue; Redler, Andreas; Topgaard, Daniel; Schmidt, Claudia; Kitzerow, Heinz-Siegfried (Colloid and Polymer Science)
Keywords: Materials Chemistry; Colloid and Surface Chemistry; Polymers and Plastics; Physical and Theoretical Chemistry

Three-dimensional structure in holographic polymer-dispersed liquid crystals - Redler, Andreas; Kitzerow, Heinz-Siegfried (Polymers for Advanced Technologies)
Keywords: Polymers and Plastics

New experiments for the quantification of counterion condensation - Huber, Klaus; Scheler, Ulrich (Current Opinion in Colloid & Interface Science)
Keywords: Colloid and Surface Chemistry; Polymers and Plastics; Physical and Theoretical Chemistry; Surfaces and Interfaces

Upper Critical Solution Temperature of Poly(N-acryloyl glycinamide) in Water: A Concealed Property - Seuring, Jan; Bayer, Frank M.; Huber, Klaus; Agarwal, Seema (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Novel drug delivery systems: Chitosan conjugates covalently attached to steroids with potential anticancer and agrochemical activity - Pérez Quiñones, Javier; Szopko, Richard; Schmidt, Claudia; Peniche Covas, Carlos (Carbohydrate Polymers)
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry

Coil-Collapse and Coil-Aggregation due to the Interaction of Cu2+ and Ca2+ Ions with Anionic Polyacylate Chains in Dilute Solution - Lages, S.; Michels, R.; Huber, Klaus (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Formation of Ca2+-Induced Intermediate Necklace Structures of Polyacrylate Chains - Lages, Sebastian; Lindner, Peter; Sinha, Prashant; Kiriy, Anton; Stamm, Manfred; Huber, Klaus (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

UV-photopolymerisation of poly(methyl methacrylate)-based inorganic–organic hybrid coatings and bulk samples reinforced with methacrylate-modified zirconium oxocluster - Graziola, Francesco; Girardi, Fabrizio; Bauer, Matthias; Di Maggio, Rosa; Rovezzi, Mauro; Bertagnolli, Helmut; Sada, Cinzia; Rossetto, Gilberto; Gross, Silvia (Polymer)
Keywords: Polymers and Plastics; Materials Chemistry; Organic Chemistry

Director Orientation of Nematic Side-Chain Liquid Crystalline Polymers Under Shear Flow: Comparison of a Flow-Aligning and a Non-Flow-Aligning Polysiloxane - Siebert, Hartmut; Quijada-Garrido, Isabel; Vermant, Jan; Noirez, Laurence; Burghardt, Wesley R.; Schmidt, Claudia (Macromolecular Chemistry and Physics)
Keywords: Materials Chemistry; Organic Chemistry; Polymers and Plastics; Physical and Theoretical Chemistry; Condensed Matter Physics

Lyotropic Lamellar Polysiloxanes with Isomeric Amphiphilic Side Chains - Burgemeister, Daniel; Farrell, Tony; Schmidt, Claudia (Macromolecular Chemistry and Physics)
Keywords: Materials Chemistry; Organic Chemistry; Polymers and Plastics; Physical and Theoretical Chemistry; Condensed Matter Physics

Lamellar Liquid Single Crystal Hydrogels: Synthesis and Investigation of Anisotropic Water Diffusion and Swelling - Kleinschmidt, Felix; Hickl, Markus; Saalwächter, Kay; Schmidt, Claudia; Finkelmann, Heino (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Shear-Induced Order in Nematic Polymers - Becker, Patrick; Siebert, Hartmut; Noirez, Laurence; Schmidt, Claudia (Macromolecular Symposia)
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry; Condensed Matter Physics

Silsesquioxane Molecules and Polystyrene Chains as a Model System for Colloid−Polymer Mixtures in the Protein Limit - Kramer, Thomas; Schweins, Ralf; Huber, Klaus (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Coil Dimensions of Polystyrene Chains in Colloid−Polymer Mixtures at the Protein Limit: A SANS Study - Kramer, Thomas; Schweins, Ralf; Huber, Klaus (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Static and dynamic scattering from block copolymeric ring molecules - Huber, Klaus (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Scattering behavior of wormlike star macromolecules - Huber, Klaus; Burchard, Walther (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Block copolymers with rigid and flexible segments - Huber, Klaus (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Remarks on A2, hydrodynamic coil expansion, and concentration dependence of the diffusion coefficient for polystyrene in toluene - Huber, Klaus; Burchard, Walther; Akcasu, A. Ziya (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Hydrodynamic and thermodynamic behavior of short-chain polystyrene in toluene and cyclohexane at 34.5.degree.C - Huber, Klaus; Bantle, Siegfried; Lutz, Pierre; Burchard, Walther (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Semidilute solutions of star branched polystyrene: a light and neutron scattering study - Huber, Klaus; Bantle, Siegfried; Burchard, Walther; Fetters, Lewis J. (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Osmotic second virial coefficient and two-parameter theories - Huber, Klaus; Stockmayer, Walter H. (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Dynamic light scattering from regular star-branched molecules - Huber, Klaus; Burchard, Walter; Fetters, Lewis J. (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Surface modification of epoxy-functionalized acrylate colloids - Kramer, Thomas; Röder, Thorsten; Huber, Klaus; Kitzerow, Heinz-Siegfried (Polymers for Advanced Technologies)
Keywords: Polymers and Plastics

Particle scattering factor of pearl necklace chains - Schweins, Ralf; Huber, Klaus (Macromolecular Symposia)
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry; Condensed Matter Physics

Surface modification of epoxy-functionalized acrylate colloids - Kramer, Thomas; Röder, Thorsten; Huber, Klaus; Kitzerow, Heinz-Siegfried (Polymers for Advanced Technologies)
Keywords: Polymers and Plastics

Calcium Induced Shrinking of NaPA Chains: A SANS Investigation of Single Chain Behavior - Schweins, Ralf; Lindner, Peter; Huber, Klaus (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Dilute solution behaviour of sodium polyacrylate chains in aqueous NaCl solutions - Schweins, Ralf; Hollmann, Jutta; Huber, Klaus (Polymer)
Keywords: Polymers and Plastics; Materials Chemistry; Organic Chemistry

Preparation of Positively and Negatively Charged Organic Colloids from a Single Precursor - Röder, Thorsten; Kramer, Thomas; Huber, Klaus; Kitzerow, Heinz-Siegfried (Macromolecular Chemistry and Physics)
Keywords: Materials Chemistry; Organic Chemistry; Polymers and Plastics; Physical and Theoretical Chemistry; Condensed Matter Physics

Quasi-elastic scattering by semiflexible rings - Huber, Klaus; Stockmayer, Walter H.; Soda, Kunitsugu (Polymer)
Keywords: Polymers and Plastics; Materials Chemistry; Organic Chemistry

Monte Carlo calculations in comparison to neutron scattering studies: 3. On the structure of 12-arm star molecules - Huber, Klaus; Burchard, Walther; Bantle, Siegfried; Fetters, Lewis J. (Polymer)
Keywords: Polymers and Plastics; Materials Chemistry; Organic Chemistry

Monte Carlo calculations in comparison to neutron scattering studies: 2. Global dimensions of 12-arm stars - Huber, Klaus; Burchard, Walther; Bantle, Siegfried; J.^Fetters, Lewis (Polymer)
Keywords: Polymers and Plastics; Materials Chemistry; Organic Chemistry

Monte Carlo calculations in comparison to neutron scattering studies: 1. Linear chains - Huber, Klaus; Burchard, Walther; Bantle, Siegfried (Polymer)
Keywords: Polymers and Plastics; Materials Chemistry; Organic Chemistry

First cumulant of the dynamic structure factor for rigid rings - Huber, Klaus; Stockmayer, Walter H. (Polymer)
Keywords: Polymers and Plastics; Materials Chemistry; Organic Chemistry

Ca2+ and Cu2+ Induced Conformational Changes of Sodium Polymethacrylate in Dilute Aqueous Solution - Ikeda, Yuko; Beer, Michael; Schmidt, Manfred; Huber, Klaus (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Flow Behavior of Two Side-Chain Liquid Crystal Polymers Studied by Transient Rheology - Quijada-Garrido, Isabel; Siebert, Hartmut; Friedrich, Christian; Schmidt, Claudia (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Lamellar lyomesophases under shear as studied by deuterium nuclear magnetic resonance - Lukaschek, M.; Müller, S.; Hasennindl, A.; Schmidt, Claudia; Grabowski, D. A. (Colloid & Polymer Science)
Keywords: Materials Chemistry; Colloid and Surface Chemistry; Polymers and Plastics; Physical and Theoretical Chemistry

Solid State NMR Investigation of C1-Deuterated Poly(di-n-hexylsilylene) - Müller, Christian; Schmidt, Claudia; Frey, Holger (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Amphiphilic liquid-crystalline networks — phase behavior and alignment by mechanical fields - Fischer, Peter; Schmidt, Claudia; Finkelmann, Heino (Macromolecular Rapid Communications)
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry

Simultaneous Measurement of Shear Viscosity and Director Orientation of a Side-Chain Liquid-Crystalline Polymer by Rheo-NMR - Grabowski, D. A.; Schmidt, Claudia (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Nematic elastomers beyond the critical point - Disch, Stefan; Schmidt, Claudia; Finkelmann, Heino (Macromolecular Rapid Communications)
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry

Utility of a liquid crystalline diacrylate for bistable switching cholesteric gel displays - Behrens, Ulrike; Kitzerow, Heinz-Siegfried (Polymers for Advanced Technologies)
Keywords: Polymers and Plastics